Assessment of the quality of the healing process in experimentally induced skin lesions treated with autologous platelet concentrate associated or unassociated with allogeneic mesenchymal stem cells: preliminary results in a large animal model - Iacopetti, Ilaria; Perazzi, Anna; Patruno, Marco; Contiero, Barbara; Carolo, Anna; Martinello, Tiziana; Melotti, Luca (Frontiers in Veterinary Science, 2023)
Regenerative medicine for the treatment of skin lesions is an innovative and rapidly developing field that aims to promote wound healing and restore the skin to its original condition before injury. Over the years, different topical treatments have been evaluated to improve skin wound healing and, among them, mesenchymal stem cells (MSC) and platelet-rich plasma (PRP) have shown promising results for this purpose. This study sought to evaluate the quality of the healing process in experimentally induced full-thickness skin lesions treated with PRP associated or unassociated with MSCs in a sheep second intention wound healing model. After having surgically created full-thickness wounds on the back of three sheep, the wound healing process was assessed by performing clinical evaluations, histopathological examinations, and molecular analysis. Treated wounds showed a reduction of inflammation and contraction along with an increased re-epithelialization rate and better maturation of the granulation tissue compared to untreated lesions. In particular, the combined treatment regulated the expression of collagen types I and III resulting in a proper resolution of the granulation tissue as observed in untreated wounds; moreover, it led to a better maturation and organization of skin adnexa and collagen fibers in the repaired skin compared to untreated and PRP-treated wounds. Overall, both treatments improved the wound healing process compared to the untreated wounds. Wounds treated with PRP and MSCs showed a healing progression that qualitatively resembles a restitutio ad integrum of the repaired skin, showing features typical of a mature healthy dermis.